1987
DOI: 10.1159/000146354
|View full text |Cite
|
Sign up to set email alerts
|

Correlative Light and Scanning Electron-Microscopic Study of Feline Gastric Mucosa: The Cardiac Region (<i>Pars cardiaca</i>)

Abstract: The cardiac region (pars cardiaca) of the cat’s stomach was examined with light and scanning electron microscopy. The glands are simple, coiled tubular, and contain mucus-secreting cells. Their surfaces are covered with microvilli which are concentrated on the boundaries of the mucus-secreting cells. A few cells interposed between the glandular cells are probably G cells. They are identified by apical projections of long microvilli into the lumen of the gland. The surface epithelial cells lining the cardiac re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…In the present study, there was marked variation in the level of the insertion of the PEL to the end of the esophagus where the point of attachment of PEL was to the esophageal side in one dog while to gastric cardiac side in three dog's similar results revealed by Pratschke et al (2004). Scanning electron microscopy in our study was identified the morphological change between the esophageal mucosa and gastric mucosa infront, within and behind the GEJ, similar results by Henk et al (1986); Al-tikriti et al (1987).…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, there was marked variation in the level of the insertion of the PEL to the end of the esophagus where the point of attachment of PEL was to the esophageal side in one dog while to gastric cardiac side in three dog's similar results revealed by Pratschke et al (2004). Scanning electron microscopy in our study was identified the morphological change between the esophageal mucosa and gastric mucosa infront, within and behind the GEJ, similar results by Henk et al (1986); Al-tikriti et al (1987).…”
Section: Discussionsupporting
confidence: 88%
“…However, there is currently only scant published material on this small vomit-competent species, either on the morphology or histology of GIT structural components that involve reflux and emesis [Liebermann-Meffert et al, 1979;Darmani and Ray, 2009]. The morphology and neurophysiology of the LES in larger species, including humans, have been studied in comparatively greater detail [Hattori and Yamanouchi, 1984;Al-Tikriti et al, 1987;Barnette et al, 1992;Blackshaw et al, 1995;Fein et al, 1999;Chandrasoma, et al, 2000]. This study illustrates the unique role of the LES through its distinctive morphological features, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…and the clinical importance of this junction have been studied in several species, including dogs [Alsafy and ElGendy, 2012], frogs [Yoshida, 2001], opossums [Seelig and Goyal, 1978], rats [Saegusa et al, 2011], cats [Al-Tikriti et al, 1987], house musk shrews [Takeuchi and Yoshioka, 2004] and humans [Nakanishi et al, 2007]. The closeness of the least shrew to primates including humans provides an excellent research model for functional physiological and pharmacological studies.…”
mentioning
confidence: 99%
“…Reticular tissue being a type of connective tissue performs the support function and the function of a microenvironment for lymphoid elements. Architectonics of reticular fibers in various structural and functional zones of lymphatic zones is unequal [172,275]. In the cortex area of a lymph node networks of reticular tissues are woven-like and in paracortex zones they are honeycomb-like, and in Billroth's strand they are felt-like, and in lymphatic nodes they are evenly coarse-grained.…”
Section: Stomach Wall Immune Structuresmentioning
confidence: 99%